1981
DOI: 10.1029/jc086ic06p05247
|View full text |Cite
|
Sign up to set email alerts
|

Observation of spectrally resolved infrared chemiluminescence from vibrationally excited O3(v3)

Abstract: Infrared emission from the v3 band of ozone near 9.6/•m has been observed in the COCHISE cryogenic chemical reactor/spectrometer. Vibrationally excited 03, formed principally by recombination of 02 with discharge-produced oxygen atoms at I torr and 80-120 K, is expanded into a low-pressure (~3 mtorr) environment where its infrared radiation is observed without interference from infrared background effects. The observed spectral distributions are interpreted by using a least squares/spectral synthesis method, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Representative limb spectra between 9 and 12 #m are shown in Figure 1 for selected tangent altitudes in a single, sunlit spatial scan. The characteristic spectral feature which is observed in this wavelength region has the intensity, spectral structure, and altitude dependence expected for the O3(v3) band as previously identified in rocket-borne [Stair et al, 1974;Stair et al, 1983;Rawlins et al, 1985] and laboratory [Rawlins et al, 1981b] measurements. This identification is further borne out by the detailed spectroscopic analysis de- result is obtained from inspection of the SPIRE CO2(¾2) limb radiances at 15 #m [Stair et al, 1985;Caledonia et al, 1985].…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Representative limb spectra between 9 and 12 #m are shown in Figure 1 for selected tangent altitudes in a single, sunlit spatial scan. The characteristic spectral feature which is observed in this wavelength region has the intensity, spectral structure, and altitude dependence expected for the O3(v3) band as previously identified in rocket-borne [Stair et al, 1974;Stair et al, 1983;Rawlins et al, 1985] and laboratory [Rawlins et al, 1981b] measurements. This identification is further borne out by the detailed spectroscopic analysis de- result is obtained from inspection of the SPIRE CO2(¾2) limb radiances at 15 #m [Stair et al, 1985;Caledonia et al, 1985].…”
supporting
confidence: 70%
“…The tailing of the emission to long wavelengths is characteristic of emission from higher-lying vibrational levels of the v3 mode, whose band centers are slightly red-shifted owing to the anharmonic effect. Thus, to analyze the spectral data for populations of individual vibrational levels, we employ a generalized spectral fitting technique [Caledonia et al, 1979; Raw-lins et al, 1981a] previously used on laboratory and field spectra of O3(v) emission [Rawlins et al, 1981b. In the following discussion we use the standard spectroscopic nomenclature for the vibrational quantum numbers of O3(/)1/)2/33), where subscripts 1, 2, and 3 denote motions in the symmetric stretch, bend, and asymmetric stretch modes, respectively [Herzberg, 1945].…”
Section: Number Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…and band intensity, particularly at such high altitudes. Although some evidence for a similar electron-related O3(v) excitation effect has been seen in laboratory discharges[Rawlins et al, 1981b], none of the reactions we discuss here have been identified or quantified in the laboratory. Indeed, the local 03 number density may actually decrease somewhat due to aurorally enhanced oddhydrogen chemistry, as has been noted in the case of solar proton events[Solomon et al, 1983].…”
mentioning
confidence: 76%
“…These were estimated using the anharmonic oscillator/rigid rotor approximation developed for the analysis of COCHISE chemiluminescence data [Rawlins et al, 1981b] and subsequently used in analysis of HIRIS and SPIRE [Green et al, 1985] data. These were estimated using the anharmonic oscillator/rigid rotor approximation developed for the analysis of COCHISE chemiluminescence data [Rawlins et al, 1981b] and subsequently used in analysis of HIRIS and SPIRE [Green et al, 1985] data.…”
Section: O Q-o3(1)3)-o Products (R6)mentioning
confidence: 99%